Colloquy with Jim Macnamara: Listening, the missing essential in communication - Bellido, Gema (Church, Communication and Culture, 2023)
In this conversation with Jim Macnamara, relevant issues about the challenges of public communication are discussed. Macnamara is Distinguished Professor of Public Communication at the University of Technology Sydney (UTS) and has conducted numerous studies with different organizations (governments, public and private companies) that have led him to the conclusion that there is need for two-way communication between organizations and their different stakeholders. His research has focused on the particular importance of listening in organizations as the missing essential in public communication: based on his research he has theorized the design of an architecture of listening and the seven canons of listening. Professor Macnamara argues that one of the reasons for the lack of trust in society has to do with the limited understanding of communication as unidirectional (one-way transmission of information); thus, people do not feel listened to by either governments or organizations.